3m-5=-8(6+5n)

Simple and best practice solution for 3m-5=-8(6+5n) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-5=-8(6+5n) equation:


Simplifying
3m + -5 = -8(6 + 5n)

Reorder the terms:
-5 + 3m = -8(6 + 5n)
-5 + 3m = (6 * -8 + 5n * -8)
-5 + 3m = (-48 + -40n)

Solving
-5 + 3m = -48 + -40n

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 3m = -48 + 5 + -40n

Combine like terms: -5 + 5 = 0
0 + 3m = -48 + 5 + -40n
3m = -48 + 5 + -40n

Combine like terms: -48 + 5 = -43
3m = -43 + -40n

Divide each side by '3'.
m = -14.33333333 + -13.33333333n

Simplifying
m = -14.33333333 + -13.33333333n

See similar equations:

| 2x+33= | | 40=8d | | 3(r-4)=19 | | 3x+5y=-58 | | -3(4p+6)-2(1-14p)=3(3+5p) | | 12+(-3*2)= | | 3z-7=5a+33 | | 9[5-3(x+2)]= | | (1-ax)*(2x+1)= | | 5x+8-12x+6= | | 6n+4=3n+12 | | -15+5z=2+1 | | 17r+8=42 | | -4c=-416 | | 14y+-94=816 | | -18+7x=-x^2 | | -4x^2+6x-(-2)=0 | | 10(-1.5)+10y=-100 | | m*14=175 | | 6t=#(t+4)+t | | 15+8y=3y | | 4x+7y=-80 | | 5p=100 | | 6q-4=-1 | | 8d-5=9d-8 | | W*2=97 | | -6x+2x-5x=0 | | 8d-5=9d-7 | | 0.07=50x | | 4*j=12.4 | | -3a(t+5)+(4t+2)=8 | | 3(x-6)=x*2 |

Equations solver categories